Organizational resilience process: Integrated model of safety culture - Hira Hafeez; Muhammad Ibrahim Abdullah; Muhammad Asif Zaheer; Qurratulain Ahsan (Organization Management Journal (OMJ), 2022)
Purpose - The purpose of the study is to create substantial awareness for safety precautions and safety parameters to lessen occupational injuries and accidents. Utilization of safety culture phenomenon with its fundamental understanding has imperative consideration for safety compliance and participation behaviors. Thoughtful aim of this study is the extension of knowledge related to safety orientation particularly in primary health-care workforce. Design/methodology/approach - Only slips and trips accounted for 40% of workplace injuries in nursing professionals. To identity, the data were collected through structured surveys from nursing professionals of public and private hospitals in Pakistan. To evaluate that data for current study, standardized regression coefficients (parameter estimation) with 95% confidence interval and 5,000 bootstrap samples were subjected. Confirmatory factor analysis was also used to measure the validity of study constructs. Findings - The potential findings of present study have assured the presence of safety culture at workplace has potential to influences negative safety outcomes. In addition, safety compliance and safety participation as mediation paths would be the strengthening addition to safety model. These findings have extended the existing understanding of compliance and participation behaviors from single factor to two different constructs of safety orientation. This safety culture model offers an evidence-based approach to nursing practitioners and nursing managers with implications for nurse's safety, education and training. Originality/value - Occupational injuries and accidental happenings have adversely affecting the quality of care, patient's recovery spam, satisfaction level and psychological health in care agents. This study has proposed a comprehensive model for understanding the mechanism of possible and reliable safety implications at health-care units. Prior knowledge has limitation to the inevitable effects of occupational injuries only rather than focusing on corrective actions against this phenomenon.
Keywords: 650; Safety culture; Safety compliance; Safety participation; Occupational injuries and accident rate; Nursing; Pakistan